Assessment of lower urinary tract symptoms among calcium channel blocker-users and its impact on quality of life - Muhammad Salman; Amer Hayat Khan; Syed Azhar Syed Sulaiman; Jeffery David Hughes; Junaid Habib Khan; Naureen Shehzadi; Khalid Hussain (Journal of the Pakistan Medical Association, 2021)
Objective: to investigate the prevalence and severity of lower urinary tract symptoms (LUTS) among calcium channel blocker (CCB) users and its impact on patients’ quality of life (QOL) Methods: This cross-sectional study was conducted among CCB-users, recruited using convenience sampling, at one hospital and 2 community pharmacies at Lahore, Pakistan during November 2017-July 2018. Urdu version of the International Prostate Symptom Score (IPSS) and EQ-5D-3L were used to assess LUTS and QOL, respectively. All data were entered and analyzed using SPSS version 22. Results: The median age of the study participants (N = 410) was 50.84, with majority of males. Around 26% of study participants were on CCB monotherapy whereas 73.7% were on CCB combinations with other antihypertensive agents. Overall prevalence of LUTS was 74.9%, with storage symptoms more common than voiding. The most common troublesome symptom was nocturia (89.5%) followed by increased daytime urinary frequency (87.1%). Median IPSS-QOL index, EQ-5D index and EQVAS score in our participants were 3, 0.621 and 60, respectively. Moreover, LUTS were significantly associated with reduced QOL (mean rank IPSS QOL-index: none-mild = 156.76 and moderate-severe = 221.85, p < 0.001; median EQ 5D index; none-mild = 0.796 and moderate-severe = 0.416; mean rank EQ-VAS: none-mild = 228.51, moderate-severe = 197.78, p = 0.022). Conclusion: Around 75% of CCB-users suffer from clinically significant LUTS which is associated with significant reduction in patient’s QOL. An earlier detection and management of LUTS by healthcare provider among CCB-users may and improve the overall QOL. Continuous...